Shaping the network society : the new role of civil society in cyberspace - Schuler, Douglas; Day, Peter, 1954- (MIT Press, 2004)
Information and computer technologies are used every day by real people with real needs. The authors contributing to Shaping the Network Society describe how technology can be used effectively by communities, activists, and citizens to meet society's challenges. In their vision, computer professionals are concerned less with bits, bytes, and algorithms and more with productive partnerships that engage both researchers and community activists. These collaborations are producing important sociotechnical work that will affect the future of the network society. Traditionally, academic research on real-world users of technology has been neglected or even discouraged. The authors contributing to this book are working to fill this gap; their theoretical and practical discussions illustrate a new orientation -- research that works with people in their natural social environments, uses common language rather than rarefied academic discourse, and takes a pragmatic perspective. The topics they consider are key to democratization and social change. They include human rights in the "global billboard society"; public computing in Toledo, Ohio; public digital culture in Amsterdam; "civil networking" in the former Yugoslavia; information technology and the international public sphere; "historical archaeologies" of community networks; "technobiographical" reflections on the future; libraries as information commons; and globalization and media democracy, as illustrated by Indymedia, a global collective of independent media organizations